Bates Motel. Season one [videorecording (DVD)] - Cuse, Carlton; Ehrin, Kerry; Cipriano, Anthony S., 1975- (Universal Studios Home Entertainment, 2013)
A modern day re-imagining of, and prequel to, the classic film Psycho. The story follows Norman Bates' teenage years, delving into his intricate relationship with his mother, and how she helped forge the most infamous serial killer of them all.